2019
DOI: 10.1177/2632010x19868462
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Solitary Fibrous Tumour of the Breast Mimicking a Benign Tumor

Abstract: Solitary fibrous tumour (SFT) of the breast is exceedingly uncommon. Radiological assessment usually shows benign features. We report on a case of malignant SFT of the breast, while emphasizing the need for additional immunostains to reach a definitive diagnosis. Standard treatment consists of lesion removal with adequate margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Similar to SFT in any other location, complete surgical resection is the optimum treatment. Close and long-term follow-up, to monitor local or distant relapses, should be considered in both benign and malignant cases [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SFT in any other location, complete surgical resection is the optimum treatment. Close and long-term follow-up, to monitor local or distant relapses, should be considered in both benign and malignant cases [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following our review of the literature, we found that the follow-up for breast SFT ranged from 5 to 132 months, with a local recurrence that was reported in only two cases, one treated by re-excision and the other by mastectomy. No disease-related deaths were reported [ 2 , 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 Breast SFT often presents as a hypoechoic or inhomogeneous echoic hypervascular mass with benign features such as well-defined margins and smooth echostructure at the radiological work-up. 6 Elastography on the US is not hard. 3 Breast SFT can be shown as a relatively well-defined mass without calcifications on mammography, 9,19 and this lesion was radiologically classified under the BI-RADS category 3 18,19 or category 4.…”
Section: Discussionmentioning
confidence: 99%
“…3 Breast SFT can be shown as a relatively well-defined mass without calcifications on mammography, 9,19 and this lesion was radiologically classified under the BI-RADS category 3 18,19 or category 4. 2,10 While malignant SFTs often presented a focal lobulated appearance 3,6,21 and were often classified as BI-RADS 4C by radiologists. 3,6,21 Generally, the surgical specimen presents as a welldefined solid mass with clear boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation